Is Technical-Grade Chlordane an Obesogen? - Silva, Juliana F.; Moreira, Bruno P.; Rato, Luís; de Lourdes Pereira, Maria; Oliveira, Pedro F.; Alves, Marco G. (Current Medicinal Chemistry, 2021)
The prevalence of obesity has tripled in recent decades and is now considered an alarming public health problem. In recent years, a group of endocrine disruptors, known as obesogens, have been directly linked to the obesity epidemic. Its etiology is generally associated with a sedentary lifestyle, a high-fat diet and genetic predisposition, but environmental factors, such as obesogens, have also been reported as contributors for this pathology. In brief, obesogens are exogenous chemical compounds that alter metabolic processes and/or energy balance and appetite, thus predisposing to weight gain. Although this theory is still recent, the number of compounds with suspected obesogenic activity has steadily increased over the years, though many of them remain a matter of debate. Technical-grade chlordane is an organochlorine pesticide widely present in the environment, albeit at low concentrations. Highly lipophilic compounds can be metabolized by humans and animals into more toxic and stable compounds that are stored in fat tissue and consequently pose a danger to the human body, including the physiology of adipose tissue, which plays an important role in weight regulation. In addition, technical-grade chlordane is classified as a persistent organic pollutant, a group of chemicals whose epidemiological studies are associated with metabolic disorders, including obesity. Herein, we discuss the emerging roles of obesogens as threats to public health. We particularly discuss the relevance of chlordane persistence in the environment and how its effects on human and animal health provide evidence for its role as an endocrine disruptor with possible obesogenic activity.
Keywords: persistent organic pollutant